Growth in children on renal replacement therapy: a shrinking problem? - Hartung, Erum A. (2013)
Growth failure has been almost inextricably linked with chronic kidney disease (CKD) and end-stage renal disease (ESRD) since initial reports of renal dwarfism dating back to the turn of the 20(th) century. Growth failure in CKD has been associated with both increased morbidity and mortality. Growth failure in the setting of kidney disease is multifactorial, and is related to poor nutritional status as well as co-morbidities such as anemia, bone and mineral disorders, and alterations in hormonal responses, as well as to aspects of treatment such as steroid exposure. In this issue of Pediatric Nephrology, Franke et al report on the gains made in growth and maturation in pediatric patients with ESRD in recent decades, particularly in Germany. Through advances in the care of CKD and ESRD over recent decades, the prevalence of growth failure appears to be decreasing. These findings, along with a recent report demonstrating decreases in mortality in childhood ESRD in the United States Renal Data System (USRDS), suggest overall improvements in the outcomes of care, perhaps reflecting improvements in the quality of care for children with kidney disease worldwide.